The use of Artificial Intelligence in Academic Research for University Higher Education: A literature review from 2014 to 2024 - Salazar-Sandoval, Augusto; Torres-Quiroz, Almintor; Vallejos-Zuta, Alex; Aguilar-Loyaga, Santiago; Alvarado-Bravo, Nestor; Aldana-Trejo, Florcita; Grados-Espinoza, Anna (LACCEI, 2025)
This study conducts a systematic review on the application of Artificial Intelligence (AI) in academic research for higher education, focusing on the period 2014-2024, in the context of the remarkable increase in scientific production and current technological trends. The main objective of the review is to analyze the use of AI in this field; in addition to identifying trends, challenges and opportunities that contribute to the improvement of educational quality and institutional management. For this purpose, the PRISMA methodology was used, using databases such as Scopus, Scielo and Google Scholar, with inclusion and exclusion criteria that allowed the selection of 14 studies out of a total of 113 analyzed. The results obtained reveal that AI is used in areas such as personalization of learning, automation of administrative tasks, research and library services, virtual assistants and development of future skills. Therefore, although with great potential to transform higher education, the integration of AI must be managed with caution to maximize its benefits and mitigate the associated risks, being crucial the training of students and professionals in skills linked to AI for an adequate adaptation.